2000
DOI: 10.1080/01411920050000962
|View full text |Cite
|
Sign up to set email alerts
|

Volunteer Support in the Primary Classroom: The long‐term impact of one initiative upon children's reading performance

Abstract: This article reports an evaluation of the effectiveness of a volunteer tutor reading intervention. Volunteers were provided with instruction and supervision in order that they might assist class teachers in the teaching of reading. A strong emphasis upon phonological awareness and storytelling underpinned the programme. Intervention took place in reception classes in three socially disadvantaged schools that could provide parallel classes to serve as controls. Assessment immediately after the intervention, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Much has been written about the influences of home and school on children's achievement (see, inter alia: Edwards and Warin 1999;Elliott, Arthurs, and Williams 2000;Farrow, Tymms, and Henderson 1999). Yet, little is known about how the dual contexts of home and school may impact upon children's confidence and perceptions of themselves as learners.…”
Section: Introductionmentioning
confidence: 98%
“…Much has been written about the influences of home and school on children's achievement (see, inter alia: Edwards and Warin 1999;Elliott, Arthurs, and Williams 2000;Farrow, Tymms, and Henderson 1999). Yet, little is known about how the dual contexts of home and school may impact upon children's confidence and perceptions of themselves as learners.…”
Section: Introductionmentioning
confidence: 98%
“…I was particularly interested in a chapter dealing with the contribution of teaching assistants, where it was found that these did not have an effect upon children's progress in literacy and mathematics despite the stated perceptions of many of the classroom staff involved. In line with earlier studies (Moyles & Suschitzky, 1997;Elliott et al, 2000) that highlight the difficulties of utilising additional adults in meaningful ways, the study provides rich and detailed case study accounts that highlight the complexities involved.…”
Section: Lorna Roberts Manchester Metropolitan University Ukmentioning
confidence: 53%
“…Peer tutoring can provide students with timely feedback (Bloom, 1984;Merrill, Reiser, Merrill & Landes 1992), increased time on task (Delquadri, Greenwood, Whorton, Carta & Hall,, 1986) and more appropriate pacing (Shanahan, 1998). Tutoring programs are expected to improve socio-emotional outcomes, such as self-efficacy (Elliott, Arthurs & Williams, 2000), self-confidence (Margolis, 2005), and child's confidence in the academic subject tutored (Koh, Sanders & Meyer, 2012). Peer tutoring could help improve social ties between tutees and tutors (Goodlad & Hirst, 1989), strengthen children's attachment to the school and improve attendance (Pridmore, Stephens & Stephens, 2000).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Secondary outcomes are outcomes that are not priority of the review, but are important for explaining effects (O'Connor, Green & Higgins, 2008). Tutoring is theorized to rely not only on cognitive, but also socio-emotional outcomes (Robinson, Schofield & Steers-Wentzell, 2005), such as confidence (Koh et al, 2012), self-efficacy (Elliott et al, 2000) and self-confidence (Margolis, 2005). Therefore, although academic outcomes were the primary aim of the review, socio-emotional results, if available, were included as secondary outcomes.…”
Section: Inclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation